Effect of maternal age on fetal weight - Rana, Sadikchya Singh (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Teenage childbearing is linked to a host of negative social, economic and medical consequences for both mother and child. Maternal mortality among girls under 18 years is two to five times higher than that of women in their 20s. This study was conducted to determine the relationship between maternal age on fetal weight. Method: It was a prospective, hospital based study, carried out in 491 primigravidas with fullterm singleton pregnancy. The study population was divided into two groups, women who were 19 and less than 19 years of age and women who were more than 19 years of age. Fetal weight as the outcome variable was compared between these groups. Results: The age of the mother ranged from 16 to 37 years. 24.8% women in the study population were <19 years of age. Although the difference was not clinically significant (p=0.51), 1/3rd of the mothers who were <19 had low birth weight. Conclusion: the relation of low birth weight and young maternal age could not be proven in this study. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6457 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 15-17